The Anjuman-i-Islam: brief profiles of its prominent members - Mansor Majdin, Mohamad Firdaus; Zakariya, Hafiz (Global Business Entreprenueurship, 2019)
The Anjuman-i-Islam was established in 1921 during Khwaja Kamaluddin’s visit to Singapore. In fact, Anjuman-i- Islam, was considered as a branch of Khwaja Kamaluddin’s own organization, Muslim Mission of Woking, England. Among the objectives of the Anjuman were to disseminate Islamic literature and spread the Islamic teaching; to help the Muslim Mission, Woking, in furthering its cause; and to open a Muslim reading room. The Anjuman had worked tirelessly to rally support from other Muslim organizations and societies throughout Malaya. This Islamic association primarily attracted the educated Muslims especially among the Indian Muslims and the Jawi Peranakan. However, less is known about its prominent leaders. Utilizing printed primary documents, thus, this study provides brief profiles of the prominent members of the Anjuman-i-Islam and their roles in this Islamic association.